The Development of Olympiad Oriented Mathematics Worksheets to Improve Students’ Critical Thinking Skills in Junior High School - Dian Rahmawati Davi; Sutama Sutama; Muhammad Noor Kholid (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2026)
Critical thinking remains a major challenge in junior high school mathematics learning, particularly in solving non routine problems that require reasoning and justification. Although Olympiad type (OSN) problems have strong potential to cultivate higher order thinking, their integration into regular classroom materials is still limited. This study aimed to develop Olympiad oriented (OSN) mathematics worksheets (LKPD) to address the limited availability of learning materials that foster junior high school students’ critical thinking skills, particularly in exponent topics, which are conceptually challenging and frequently tested in mathematics competitions. The Research used a Research and Development (R&D) approach with the ADDIE model (analysis, design, development, implementation, and evaluation). The worksheets were designed to scaffold and strengthen critical thinking through five indicators: interpretation, mathematization, analysis, explanation, and evaluation. The field implementation involved 29 eighth grade students at MTsS YIC Sudirman in the 2025/2026 academic year. Product quality was examined through expert validation and user responses (teacher and students), while effectiveness was evaluated using a pretest–posttest design and indicator level performance analysis. The results showed that the developed worksheets were valid, practical and effective for classroom use. Students’ achievement increased from a pretest mean of 14.77 (SD = 2.69) to a posttest mean of 23.28 (SD = 3.18). Improvements were found across all critical thinking indicators, with the most notable gains in interpretation and mathematization, followed by analysis. However, explanation and especially evaluation still required further reinforcement. Therefore, future instructional design should incorporate more tasks that explicitly require students to justify their reasoning, critique alternative solutions, and reflect on the validity of their answers to strengthen these higher order thinking components. Overall, the OSN oriented worksheets are valid, practical and effective improve students’ critical thinking skills in junior high school mathematics learning.